Tomato growth submitted to different soil water conditions using biostimulants - Peripolli, Mariane; Sgarbossa, Jaqueline; Diel , Maria Inês; Bolzan Morais, Tassiane; Müller, Érika Nogueira; Pivetta, Maicon (Comunicata Scientiae, 2024)
Stress caused by water deficit is the main factor that decreases the productivity and quality of agricultural products. The objective of this study was to describe the morphological components of tomato plants subjected to different soil water conditions, as well as elucidate the use of the Seed+ and Crop+ biostimulants as an alternative to mitigate the effects of water deficit. The experiment was conducted in a completely randomized design with 12 treatments: control; Seed+; Seed+ + Crop+ 1x; Seed+ + Crop+ 2x; Crop+ 1x; Crop+ 2x, in soil water conditions at 50% and 100% soil water retention capacity (WRC). The plant height, leaf width and length, and stem diameter variables referring to the plants were assessed under both soil water conditions and by applying biostimulants. Data were organized and adjusted to the non-linear logistic regression model in order to describe the growth of tomato plants of the Santa Cruz Kada cultivar, which proved to be adequate to describe the growth and showed the best fit; in addition, the use of the Seed+ and Crop+ biostimulants helped in the morphology of tomato plants in both water conditions and reduced the damages caused by water deficit.